How to Scaffolding in Online Learning - Nurjanah, Ayu; Ngaisah, Nur Cahyati; Awaliyah, Tuti; Al Ayyubi, Muhammad (Jurnal Pendidikan Raudhatul Athfal, 2023)
The Covid-19 outbreak that hit the world has caused learning to experience a change, which is usually face-to-face at school and has changed to online learning at home. Researchers observed the process of online learning in early childhood. Online learning is not an easy thing, many things must be prepared to support effective online learning in early childhood. Providing support (scaffolding) by both teachers and parents to create active, fun and motivating learning for children even though they are at home. This study uses a qualitative approach with phenomenological methods. The subjects of this study were class teachers and principals of the KB Islamic Kindergarten Al-Azhar 54 Pekanbaru. Data collection methods through observation, interviews, and documentation. Data analysis used the Miles and Huberman model triangulation. The results showed that the scaffolding given by teachers and parents in the Islamic Kindergarten Al-Azhar 54 Pekanbaru KB was very effective. Thus, keeping children enthusiastic about carrying out learning even though they are at home.